Analysis of Effective Communication Relationships With Interprofessional Attitudes Through Outbound Activities: Literature Review - Dhiyaulhaq, Alvira; Amanatillah, Asti; Anjelina, Dian Denisa; Khoirunnisa, Irmanda; Robbah, Mar’aa Refina; Aulia, Miftha Huda; Fanani, Erianto; Sheikh Abdullah, Siti Rozaimah (Health Frontiers: Multidisciplinary Journal for Health Professionals, 2023)
Introduction: Society can achieve a healthy condition when supported by health services quality, and prime, interprofessional collaboration is required to be good health. In order to realize good quality and optimal health services, it is necessary to implement interprofessional collaboration practices among health workers. In service health occurs error 70-80 % caused by poor communication and understanding in the team. The importance of effective interprofessional communication as a provider of quality health services is a challenge for health workers. Method:A thorough review of the literature presented in this article was conducted using analytical procedures and inclusion standards for this study. References are checked to see if they meet the following requirements: publication in English, six years source limit, and open access to abstracts and articles. For this article's research, six literature reviews were used, and keyword syntax for each database was used to search Academia edu, Google Scholar, and ResearchGate databases from 2018 to 2023. Results: Some things that need to be considered and affect health service outcomes and patient satisfaction perceptions are the ability of health workers to communicate effectively, observe, listen, explain, and empathize. Interpersonal communication is a process of conveying information (messages, ideas and ideas) from one party to another. Doing outbound gives results in increasing the level of interpersonal communication someone. Conclusion: The ability of nurses to perform at their best in order to care for patients and enhance hospital performance is dependent on interprofessional attitudes such as integrity, honesty, and leadership.